2010
DOI: 10.3892/ijo_00000653
|View full text |Cite
|
Sign up to set email alerts
|

miR-1226 targets expression of the mucin 1 oncoprotein and induces cell death

Abstract: Abstract. The MUC1 oncoprotein is aberrantly overexpressed in human carcinomas and hematologic malignancies. MicroRNAs (miRNAs) have been implicated in the suppression and induction of oncogenesis. The present studies demonstrate that the MUC1 mRNA 3' untranslated region (3'UTR) contains a highly conserved motif for binding of a novel miRNA, miR-1226, that has no known targets. The results show that miR-1226 is expressed in human breast cancer cell lines and non-malignant mammary epithelial cells. We also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…miR-1226 was reported to be involved in tumorigenesis, angiogenesis and drug resistance in breast cancer and non-small cell lung cancer [23, 24]. The correlation between hsa-miR-1226-3p and MUC1 has also been proved by the previous study which revealed that miR-1226 interacted with the MUC1 mRNA 3’ UTR and induced downregulation of MUC1 [25].…”
Section: Discussionmentioning
confidence: 95%
“…miR-1226 was reported to be involved in tumorigenesis, angiogenesis and drug resistance in breast cancer and non-small cell lung cancer [23, 24]. The correlation between hsa-miR-1226-3p and MUC1 has also been proved by the previous study which revealed that miR-1226 interacted with the MUC1 mRNA 3’ UTR and induced downregulation of MUC1 [25].…”
Section: Discussionmentioning
confidence: 95%
“…1 ). Most recently, downregulation of MUC1 expression by micro-RNA has been reported by several groups (Jin et al 2010 ; Rajabi et al 2010 ; Sachdeva and Mo 2010 ). Sachdeva and Mo showed that miR-145 directly targets MUC1 by interaction with the 3 ′ -UTR and found that miR-145 acts as a tumor suppressor in part by affecting invasion and metastasis by targeting MUC1 (Sachdeva and Mo 2010 ).…”
Section: Functional Role and Epigenetic Regulation Mechanisms Of Mucimentioning
confidence: 91%
“…In breast cancer cells, Rajabi et al indicated that miR-125b suppresses translation of the MUC1 and that miR-125b thereby functions as a tumor suppressor (Rajabi et al 2010 ). Jin et al showed that MUC1 expression is suppressed by miR-1226 and that miR-1226-induced downregulation of MUC1 is correlated with cell death of MUC1-positive breast cancer cells (Jin et al 2010 ). These findings suggest the possible functional importance of MUC1 under both physiological and pathological conditions.…”
Section: Functional Role and Epigenetic Regulation Mechanisms Of Mucimentioning
confidence: 99%
See 1 more Smart Citation
“…Interrogation of MiRbase and MiRanda databases revealed a large number of miRNAs that could potentially target the 3′-UTR of mucin genes including MUC1 , MUC4 , MUC17 or MUC2 , MUC5AC , and MUC6 [ 66 ]. Very recent data indeed indicate that the MUC1 3’-UTR is directly regulated by miR-125b, miR-145 and miR-1226 in human breast cancer cell line [ 76 , 77 , 78 ].…”
Section: Epigenetic Regulation Of Mucin Genes In Pancreatic Cancermentioning
confidence: 99%